(untitled) (Journal of Pakistan Orthopaedic Association, 2017)
ABSTRACT Involvement of spine in tuberculosis has serious implications if not diagnosed and treated in time. Paraplegia of different grades is not uncommon. The disease is more common in developing countries but in the developed countries it is also seen, majority of the patients being immigrants from TB endemic countries. Diagnosis is based on clinical judgement aided by variety of investigations, MRI being the imaging modality of choice. Treatment must be started as early as possible following WHO guidelines and patients must be followed till the eradication of the disease. Decision of surgical intervention should be taken carefully as not all patients are candidates for conservative management.